Association between Serum Neopterin and Inflammatory Activation in Chronic Kidney Disease. (26th August 2012) - Yadav, Ashok Kumar; Sharma, Vinod; Jha, Vivekanand
Abstract : Background. The serum levels of neopterin, a marker associated with cell-mediated immunity are elevated in chronic kidney disease (CKD). We evaluated serum neopterin levels and investigated its association with markers of inflammation in a cross-section of CKD subjects without known cardiovascular disease. Methods. Serum neopterin levels were measured in 118 patients with stage 3–5 CKD and 41 healthy subjects with normal kidney function (HC). Patients with known cardiovascular disease were excluded. We also estimated highly sensitive CRP (hsCRP) and interluekin-6 (IL-6), tumor necrosis factor-α (TNF-α ) and interferon-γ (IFN-γ ) in the CKD subjects. All assays were done using commercially available ELISA kits. The correlation between neopterin and markers of inflammation were investigated. Results. Of the CKD population, 82 were in stage 5 (60 stage 5 D), 24 in stage 4, and 12 in stage 3. The mean age was 51.04 ± 1.3 years and 66% were males. The commonest cause of CKD was diabetes (36%). Serum neopterin levels were 5-fold higher in CKD patients as compared to HC (74.8 ± 3.6 versus 15.0 ± 2.8  nmol/L, P < 0.0001 ). There was a graded increase of serum neopterin from stages 3 to 4 and 5. CKD 5 D patients exhibited significantly higher levels compared to nondialysis stage 5 patients (P < 0.0001 ). An inverse correlation was noted between serum neopterin and eGFR (r = − 0.359, P < 0.0001 ). Serum neopterin correlated with hsCRP (r = 0.285, P = 0.002 ), IL-6 (r = 0.212, P = 0.034 ), and IFN-γ (r = 0.32, P = 0.001 ) but not with TNF-α . Conclusion. Serum neopterin level is elevated and correlates with the severity of CKD. The elevation correlates with elevation of most, but not all, inflammatory markers. Its role in future development of cardiovascular disease and modulation with anti-inflammatory therapies needs further studies.